Respuestas

2013-08-04T00:21:17+02:00
X2-3x-18=0
(x+3)  (x-6)

X2+3x-10=0
(x+5)  (x-2)

X2-14x+49=0
(x-7)  (x-7)

X2-7X-18=0
(x-9)  (x+2)

x2-7x-12=0
este ultimo se resuelve por la formula general

espero que te sirva

¡La mejor respuesta!
2013-08-04T00:39:43+02:00
X2-3x-18=0

X2 + 3x - 10 = 0
    Factorizando
       (x + 5)(x - 2) = 0
             x + 5 = 0              x1 = - 5
             x - 2 = 0               x2 = 2                   S = {-5, 2}

X2 - 14x + 49 = 0
(x - 7)^2 0              cuadrado perfecto
                 x - 7 = 0                            x1 = x2 = 7          S = {7}

X2 - 7X - 18 = 0
         Factorizando
          (x - 9)(x + 2)
           x - 9 = 9                  x1 = 9
           x + 2 = 0                 x2 = - 2               S = {- 2, 9}

x2 - 7x - 12 = 0
   Por Báskara
     delta = b^2 - 4.a.c = (-7)^2 - 4.1.(-12) = 49 + 48 = 97
x = [- b + ó - (raiz delta)]/2
    x1 = [7 + (raiz 97)]/2
    x2 = 
[7 - (raiz 97)]/2                 S = {[7 - (raiz 97)]/2, [7 + (raiz 97)]/2}